Risk factors for admission to the pediatric critical care unit among children hospitalized with COVID-19 in France - Prévost, Blandine; Retbi, Aurélia; Binder-Foucard, Florence; Borde, Aurélie; Bruandet, Amélie; Corvol, Harriet; Gilleron, Véronique; Le Bourhis-Zaimi, Maggie; Lenne, Xavier; Muller, Joris; Ouattara, Eric; Séguret, Fabienne; et al. (Frontiers in Pediatrics, 2022)
Background: COVID-19 infection is less severe among children than among adults; however, some patients require hospitalization and even critical care. Using data from the French national medico-administrative database, we estimated the risk factors for critical care unit (CCU) admissions among pediatric COVID-19 hospitalizations, the number and characteristics of the cases during the successive waves from January 2020 to August 2021 and described death cases. Methods: We included all children (age <18) hospitalized with COVID-19 between January 1st, 2020, and August 31st, 2021. Follow-up was until September 30th, 2021 (discharge or death). Contiguous hospital stays were gathered in “care sequences”. Four epidemic waves were considered (cut off dates: August 11th 2020, January 1st 2021, and July 4th 2021). We excluded asymptomatic COVID-19 cases, post-COVID-19 diseases, and one-day-long sequences (except death cases). Risk factors for critical care unit admission were assessed with a univariable and a multivariable logistic regression model in the entire sample and stratified by age, whether younger than 2. Results: We included 7485 patients, of whom 1988 (26.6%) were admitted to the CCU. Risk factors for admission to the CCU were being younger than 7 days (OR: 3.71 95% CI [2.56-5.39]), being between 2 and 9 years old (1.19 [1.00-1.41], pediatric multisystem inflammatory syndrome (PIMS) (7.17 [5.97-8.6]) and respiratory forms (1.26 [1.12-1.41]), and having at least one underlying condition (2.66 [2.36-3.01]). Among hospitalized children younger than 2 years old, prematurity was a risk factor for CCU admission (1.89 [1.47-2.43]). The CCU admission rate gradually decreased over the waves (from 31.0% to 17.8%). There were 32 (0.4%) deaths, of which the median age was 6 years (IQR: 177 days–15.5 years). Conclusion: Some children need to be more particularly protected from a severe evolution: newborns younger than 7 days old, children aged from 2 to 13 years who are more at risk of PIMS forms and patients with at least one underlying medical condition.